Ecofisiologia de plantas jovens de mogno-africano submetidas a deficit hídrico e reidratação - ALBUQUERQUE, Marcos Paulo Ferreira de (2015)
The objective of this work was to evaluate the capacity of young plants of African mahogany (Khaya ivorensis) to recover their water status and gas exchange after water deficit. Plants with approximately 315 days, irrigated (control) and non-irrigated, were evaluated after water was withheld for 14 days, and after one, three, and seven days of irrigation resumption (rehydration). On day 14, the predawn leaf water potential (Ψam) of stressed plants was reduced to -2.66 MPa. With water deficit, significant decreases were observed in predawn relative water content (32% reduction), in net assimilation rate of CO2 (90%), in stomatal conductance (95%), in transpiration (93%), and in intercellular to ambient ratio of CO2 concentration (37%). During rehydration, the water status of stressed plants was recovered after three days. Gas exchange was also recovered, but in a slower rate than water status. Under water deficit, proline concentration increased and total soluble carbohydrate concentration decreased. Young African mahogany plants are tolerant to moderate water deficit.